Cabozantinib (XL184) and R428 (BGB324) Inhibit the Growth of Esophageal Squamous Cell Carcinoma (ESCC) - Yang, Pei-Wen; Liu, Yu-Cheng; Chang, Ya-Han; Lin, Ching-Ching; Huang, Pei-Ming; Hua, Kuo-Tai; Lee, Jang-Ming; Hsieh, Min-Shu (Frontiers in Oncology, 2019)
Esophageal squamous cell carcinoma (ESCC) is a deadly disease for which no effective targeted therapeutic agent has been approved. Both AXL and c-MET have been reported to be independent prognostic factors for ESCC. Thus, inhibitors of AXL/c-MET might have great potential as targeted therapy for ESCC. In the current study, we evaluated the therapeutic potential of the AXL/c-MET selective inhibitors, R428 and cabozantinib, in cell and mouse xenograft models. We demonstrated that both R428 and cabozantinib significantly inhibited the growth of CE81T and KYSE-70 ESCC cells and showed by wound-healing assay that they both inhibited ESCC cell migration. In the animal model, ESCC xenograft models were established by injecting KYSE70 cells with matrigel into the upper back region of NOD-SCID male mice followed by treatment with vehicle control, R428 (50 mg/kg/day), cisplatin (1.0 mg/kg) or cabozantinib (30 mg/kg/day) for the indicated number of days. R428 alone significantly inhibited ESCC tumor growth compared to the vehicle; however, no synergistic effect with cisplatin was observed. Notably, the dramatic efficacy of cabozantinib alone was observed in the mice xenograft model. Collectively, our study demonstrated that both cabozantinib and R428 inhibit ESCC growth in cell and xenograft models. The results reveal the great potential of using cabozantinib for targeted therapy of ESCC.